A formação inicial de professores para o uso das TICs: um estudo exploratório do curso de pedagogia de duas universidades da cidade de São Paulo - Oliveira, Gisele Soares Gama de (2009)
New technologies for information and knowledge have changed quickly, bringing new challenges for social development, what obligatory includes the education. To understand the features of the available technologies and how to integrate them effectively is completely crucial for introducing some of them in the classroom. Considering that the pedagogue is responsible for transmitting this kind of knowledge in the learning process, and the university is responsible for graduating properly this professional, this study was carried out in order to verify if competences and abilities for the use of these new technologies are being properly developed in the pedagogue´s graduation. Data were collected regarding to (1) providing disciplines on new technologies in the curriculum of Pedagogy School; (2) proposing reflections and contents in these disciplines, so that the student can really understand why and how integrate the computer in the educational practice; and (3) how adequate is the integration between the curricular proposal and the competences of the teachers responsible to teach these disciplines to the future Pedagogue. These data were obtained from two private universities (Universidade Presbiteriana Mackenzie UPM e Pontifícia Universidade Católica de São Paulo PUC-SP), located in São Paulo city, by means of official documents provided by them, and by applying open questions to coordinators and teachers involved with such disciplines. Qualitative analysis of these data was based on the National Curricular Emends for the Pedagogy School and on recent and relevant theoretical references on the matter. Data revealed that curricular matrix provide disciplines on new technologies according to the parameters adopted for the study, and that teachers, in the general, have developed proper competences to teach such disciplines and use the necessary resources and equipments for put theory and practice together in the formation of the future pedagogue. However, although less frequently, there are still some inadequateness resulting from what seems to be pure bureaucracy, such as the criteria for selecting these teachers and the availability of space and material technological resources, which are crucial for a better professional formation regarding the effective use of new technologies.